2004
DOI: 10.1080/15459620490264454
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Simulated Respirator Fit Factors Using Aerosol and Vapor Challenges

Abstract: Although not well established, mask leakage measured using submicron aerosol challenges is generally accepted as being representative of vapor challenges. The purpose of this study was to compare simulated respirator fit factors (FFs) measured using vapor challenges to those measured using an aerosol challenge. A full-facepiece respirator was mounted on a headform inside a small enclosure and modified with controlled leaks (laser-drilled orifices) to produce FFs ranging from about 300 to 30,000. A breathing ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Based on these results, the authors suggested that fit test utilizing a vapor or gaseous agent may be a more critical test in terms of penetration than fit tests using an aerosol. Another study indicated that the lower apparent fit factors measured with acetone vapor may be due to the vapor permeation through the filter media to increase the concentration inside the respirator (Gardner et al, 2004). Further studies showed that the simulated fit factors measured with a gaseous challenge agent sulfur hexafluoride (SF 6 ) was $25% higher than those measured for PSL aerosol challenge with no significant difference between the two test agents (Gardner et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, the authors suggested that fit test utilizing a vapor or gaseous agent may be a more critical test in terms of penetration than fit tests using an aerosol. Another study indicated that the lower apparent fit factors measured with acetone vapor may be due to the vapor permeation through the filter media to increase the concentration inside the respirator (Gardner et al, 2004). Further studies showed that the simulated fit factors measured with a gaseous challenge agent sulfur hexafluoride (SF 6 ) was $25% higher than those measured for PSL aerosol challenge with no significant difference between the two test agents (Gardner et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that the lower apparent fit factors measured with acetone vapor may be due to the vapor permeation through the filter media to increase the concentration inside the respirator (Gardner et al, 2004). Further studies showed that the simulated fit factors measured with a gaseous challenge agent sulfur hexafluoride (SF 6 ) was $25% higher than those measured for PSL aerosol challenge with no significant difference between the two test agents (Gardner et al, 2004). However, the simulated fit factor values measured using isoamyl acetate (IAA) vapor showed a significant decrease at sealed conditions and an increase at larger leak sizes than the values obtained with PSL particles.…”
Section: Discussionmentioning
confidence: 99%